2018
DOI: 10.1080/10942912.2018.1540988
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Southern Tunisian honeys based on their physicochemical and textural properties

Abstract: This study investigated the physicochemical, rheological and textural properties of nine types of honey from different regions of southern Tunisia. Principal component and cluster analyses were used to classify the honeys into groups. The physicochemical results (water, proteins, total soluble solids, pH, free acidity, water activity, electrical conductivity, invertase activity, Hydroxymethylfurfural (HMF), vitamin C, lycopene and anthocyanins) were in accordance with those of the standards Established by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(71 reference statements)
1
3
1
Order By: Relevance
“…The content of vitamin C and E. As shown in Table 1, the content of vitamin C was about 99.5% higher in beebread than in honey. Our data of ascorbic acid concentration are lower than level of this substance found in the Portuguese (Karabagias et al 2018) and Tunisian (Boussaid et al 2018) honeys. The level of vitamin C in the Brazilian bee pollen was in the range from 60.3 to 797.0 µg g -1 (Sattler et al 2015), while bee pollen harvested in Portugal was characterised by even higher content of vitamin C (46.9-214.4 mg g -1 ) (Estevinho et al 2019).…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…The content of vitamin C and E. As shown in Table 1, the content of vitamin C was about 99.5% higher in beebread than in honey. Our data of ascorbic acid concentration are lower than level of this substance found in the Portuguese (Karabagias et al 2018) and Tunisian (Boussaid et al 2018) honeys. The level of vitamin C in the Brazilian bee pollen was in the range from 60.3 to 797.0 µg g -1 (Sattler et al 2015), while bee pollen harvested in Portugal was characterised by even higher content of vitamin C (46.9-214.4 mg g -1 ) (Estevinho et al 2019).…”
Section: Resultscontrasting
confidence: 85%
“…The level of vitamin C in the Brazilian bee pollen was in the range from 60.3 to 797.0 µg g -1 (Sattler et al 2015), while bee pollen harvested in Portugal was characterised by even higher content of vitamin C (46.9-214.4 mg g -1 ) (Estevinho et al 2019). Moreover, the place of origin and the harvest period affect the concentration of bioactive substance (including vitamin C) (Sawicki et al 2019), as well as the extraction and analysis method (Wang et al 2004;Boussaid et al 2018). Another reason for low vitamin C amount in tested samples, could be pH-unstable environment.…”
Section: Resultsmentioning
confidence: 99%
“…The sucrose content of the remaining 30 samples (44.1%) was less than the legally permissible maximum value of 5%. In other work involving 9 honey samples collected from southern Tunisia it was found that the sucrose content ranged from 2.3 to 4.5% [28]. In the present study, the mean sucrose content of the 6 non-conforming samples was 14.1%, with a range of 5.1 to 33.4%.…”
Section: Total Sugar Content In Honey Samples Sucrose Contentsupporting
confidence: 47%
“…The level of non-conformity was lower than the 64.4% reported by Al-Farsi et al (2018) [6] for 58 honey samples collected from 18 geographical regions in Oman, following a comparison with Gulf Standardization Organization (GSO) standards. It is notable that Boussaid et al (2018) [28] found that all 9 honey samples examined in Tunisia complied with the Codex Alimentarius standards. In the current study, the proportion of non-conformity ranged from 5.0 to 21.0% for the various types of honey, with the lowest values noted for forest honey.…”
Section: Compliance Of Imported Honey With Standardsmentioning
confidence: 94%
See 1 more Smart Citation